Balancing Strategic Paradoxes through Paradoxical Leadership: Empirical Evidence from Digitizing Hospitals in Indonesia - Mombang Sihite; Aisyah Pia Asrunputri (Glosains: Jurnal Sains Global Indonesia, 2026)
Background: Indonesian hospitals are under intensifying pressure to digitalize, yet digital transformation (DT) does not automatically yield organizational agility a paradox that challenges conventional technology adoption frameworks. Despite government mandates such as Ministry of Health Regulation No. 24/2022 requiring electronic medical records, many hospitals remain trapped in administrative digitization without achieving strategic renewal. Objective: This study investigates the roles of Digital Transformation (DT) and Paradoxical Leadership (PL) in promoting Organizational Agility (OA) and Strategic Renewal (SR) in Indonesian hospitals, with OA as a mediator and PL as a moderator in the DT–OA relationship. Methods: A quantitative explanatory approach was employed using Partial Least Squares Structural Equation Modeling (PLS-SEM). Primary data were collected via structured questionnaire from 400 hospital managers and clinical administrators across Indonesian healthcare organizations, selected through purposive sampling. Results: The analysis reveals that DT does not directly influence OA, indicating structural limitations that hinder organizational agility. However, PL plays a significant moderating role that amplifies DT's effect on OA, demonstrating that leadership capability is crucial in managing strategic contradictions and facilitating technology adoption. Furthermore, OA proves to be the primary determinant of SR, enabling adaptive business model reconfiguration in the JKN era. Conclusion: The study confirms that the strategic success of healthcare institutions depends on the synergy between digital capabilities and managerial leadership capability in navigating organizational complexities. Paradoxical leadership is not merely a management style but a driving force that transforms digital investment into sustainable strategic renewal.